ANALISIS TINGKAT PENGETAHUAN MASYARAKAT TENTANG PENGGUNAAN OBAT KERAS DAN OBAT BEBAS - Fatiha, Aufa Putri; Ramadani, Zahrafitria; Tsany, Calista (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2024)
Weak drug regulatory supervision in developing countries allows the public to easily obtain prescription-only medicines without adequate control, including through the misuse of medical prescriptions. This situation may lead to irrational drug use and increase the risk of adverse drug reactions and other health problems. This study aims to assess the level of pharmacy compliance with regulations governing prescription-only medicines, particularly the requirement for a valid physician’s prescription. In addition, this study discusses the distinction between prescription-only medicines and non-prescription drugs. Non-prescription or over-the-counter medicines can be purchased freely in pharmacies and drugstores; however, their use must comply with label instructions and pharmacists’ guidance. Compliance with regulations and the professional role of pharmacists are essential to ensure safe, rational, and responsible drug use in the community.